Interactions entre pêcheries de lagunes, pêcheries côtières et pêche au chalut dans le golfe du Lion - Farrugio, Henri; Le Corre, Gildas (1986)
INTRODUCTION : This document is the final report concerning a study led on interactions between lagoon fisheries, coastal fisheries and trawl fishing in the Lion gulf. If any of the three components mentioned above is able to catch species of interest (or none) to the other groups, other ones are of interest to at least two components. Furthermore, within each group, interactions between various fleet and/or trade can exist. Interactions are more complex on account of the specific diversity of catches. If until 1984, trawler fleets were the subject of continuous studies, lagoon and coastal fleets were only considered on a one off basis. The goal of the work led by IFREMER concerning Mediterranean halieutic resources aims at obtaining basic elements which would allow, in time, to suggest stock management strategies and fishery development based on the understanding of the different interactions involved and on the evaluation of consequences for each set of potential measures. The maritime geographical location we have chosen for this study is the Lion gulf and more precisely Sete's maritime district as well as Port Vendres. Marine fish in this area include a very complex biotope mosaic. Some of the so called "migrating" species like sea breams, sea bass, soles, white sea breams and mullets can be found in different zones every year or during their life span. Those migrating fish are subject to intense fishing at sea and in ponds, and remarkably fishing activity follows those species migrating activity. Up until the last few years, work concerning sea breams, sea bass and soles was essentially geared towards their biology and ecology. However there also have been a few studies looking at their "population dynamics" aspect. If studies have attempted to establish links related to sea bass, sea breams and fish migration, they have been conducted on a local and one off basis. As it was, research work did not take into account all fishing activity for the exploitation of those two species in the Sete district. None of ...